Factors associated with all-cause mortality in endovascularly treated patients with chronic limb-threatening ischemia - Rašiová, Mária; Pavlíková, Veronika; Hudák, Marek; Kožár, Viktor; Dekanová, Lucia (Frontiers in Epidemiology, 2026)
BackgroundDespite advances in treatment, mortality in patients with chronic limb-threatening ischemia (CLTI) is high. The aim of our study was to evaluate 5-year all-cause mortality and factors associated with it in endovascularly treated (EVT) patients with foot ischemic ulcers.MethodsWe reviewed all patients who had undergone EVT for lower extremity peripheral artery disease between January 2016 and December 2018. Adjustments in multivariate analyses were performed for age, hypertension, diabetes mellitus, sex, smoking, dyslipidemia, chronic obstructive pulmonary disease, malignancy, atrial fibrillation, heart failure with reduced ejection fraction, coronary artery disease, postprocedural ipsilateral amputation, ipsilateral reintervention, number of endovascularly treated regions, fibrinogen and creatinine.ResultsFour hundred and fifty-one patients (155 women, 296 men) with a mean age of 70.4 ± 9.60 years were included in the analysis. The 5-year all-cause mortality was 60.5%. In multivariate analysis mortality risk was higher in women (HR 1.42; 95% CI 1.09–1.86; p = 0.010), and after EVT in two or more anatomical regions (HR 1.37; 95% CI 1.05–1.79; p = 0.022). The mortality risk was positively associated with creatinine (HR 1.003; 95% CI 1.002–1.004; p < 0.001), and fibrinogen (HR 1.19; 95% CI 1.11–1.29; p < 0.001). Ipsilateral reintervention (HR 0.67; 95%CI 0.47–0.94; p = 0.021) and ipsilateral amputation after EVT (HR 0.71; 95% CI 0.51–0.98; p = 0.037) were associated with lower all-cause mortality risk.ConclusionsFemale sex, treatment in two or more anatomical regions, creatinine and fibrinogen were associated with higher 5-year mortality risk. Lower 5-year all-cause mortality risk was observed in patients with ipsilateral reintervention and ipsilateral amputation after EVT.